DAMPAK KEPUTUSAN KONTROVERSIAL GEREJA TERHADAP LESBIAN, GAY, BISEKSUAL, TRANSGENDER - Raharjo, Ribut Prapto; Elen (STT Ekklesia Pontianak, 2023)
Abstract: The church cannot be separated from the rapid pace of development and change of the times. The church often faces attacks from outside. One of the external attacks faced by the church is the phenomenon of lesbian, gay, bisexual, and transgender who have entered the church. The church must be present and shine God's light to those who are lost. The church must uphold the authority of the Bible. Because in the history of creation, God only created male and female genders. Sexual behavior outside of male and female in a holy bond is sin. The fall of man into sin has corrupted the good of God, one of which is deviant sexual orientation or behavior. The church is not allowed to recognize the existence of homosexuality or lesbian, gay, bisexual, and transgender on the basis of genetics. The existence of churches that have recognized and accepted lesbians, gays, bisexuals and transgenders on the basis of genetics and love has led to controversy within the church itself. This study uses the grammatical method on several Bible verses and literature research with several accurate book or article references. This study found that there are churches that accept the existence of lesbians, gays, bisexuals and transgenders in the church on the grounds of genetics, love and human rights. But there are also churches that vehemently reject lesbians, gays, bisexuals and transgenders because they are considered contrary to the word of God. The controversy caused by the church when making a decision to accept lesbians, gays, bisexuals and transgenders into the church for reasons of genetics, love and human rights will damage the faith of the church generation. So that this phenomenon needs to continue to be considered progressively along with the times. Abstrak: Gereja tidak bisa dipisahkan dari laju perkembangan dan perubahan zaman yang begitu cepat. Gereja sering berhadapan dengan serangan-serangan dari luar. Salah satu serangan dari luar yang dihadapi gereja adalah fenomena lesbian, gay, biseksual, dan transgender yang sudah masuk ke dalam gereja. Gereja harus hadir dan memancarkan terang Tuhan bagi yang tersesat. Gereja harus menjunjung tinggi otoritas Alkitab. Sebab dalam sejarah penciptaan, TUHAN hanya menciptakan gender laki-laki dan perempuan. Perilaku seksual di luar laki-laki dan perempuan dalam ikatan kudus adalah dosa. Kejatuhan manusia ke dalam dosa telah merusak yang baik dari Tuhan, salah satunya adalah orientasi atau perilaku seksual menyimpang. Gereja tidak diperkenan untuk mengakui keberadaan homoseksualitas atau lesbian, gay, biseksual, dan transgender atas dasar genetika. Adanya gereja yang telah mengakui dan menerima lesbian, gay, biseksual dan transgender atas dasar genetika dan kasih telah memunculkan kontroversi di lingkup gereja sendiri. Studi ini menggunakan metode gramatikal pada beberapa ayat Alkitab dan penelitian pustaka dengan beberapa referensi buku atau artikel yang akurat. Studi ini menemukan adanya gereja yang bersikap menerima keberadaan lesbian, gay, biseksual, dan transgender di dalam gereja dengan alasan genetika, kasih dan hak asasi manusia. Tetapi ada pula gereja yang dengan keras bersikap menolak lesbian, gay, biseksual, dan transgender karena dianggap bertentangan dengan firman Tuhan. Kontroversi yang ditimbulkan oleh gereja ketika mengambil keputusan menerima lesbian, gay, biseksual, dan transgender masuk ke dalam gereja karena alasan genetika, kasih maupun hak asasi manusia akan merusak iman generasi gereja. Sehingga fenomena ini perlu untuk terus diperhatikan secara progresif seiring dengan perkembangan zaman.